Regulation of Port Charges in Spain: Global versus Local Competition - Marta Gonzalez-Aregall; Xavier Fageda (European Regional Science Association (ERSA), 2013)
This article examines the determinants of traffic volumes and the revenues per tonne generated by Spain?s port authorities. The interest of the study lies on the strong differences between port authorities in a context of strict regulation but that provides some scope for price competition. We estimate a pricing and demand equation system using instrumental variables. We find that port charges influence the amount of traffic that a port is able to generate. Furthermore, we find clear evidence of local price competition and report mixed results for global competition. Revenues per tonne are higher in ports operating more international regular lines and with multinational terminal operators, while they are lower in ports with nearby competing facilities and where the market share of the dominant shipping firm is high.
Keywords: H54; L91; R48; 330